2018
DOI: 10.1038/s41598-018-31791-x
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid in primary total knee arthroplasty without tourniquet: a randomized, controlled trial of oral versus intravenous versus topical administration

Abstract: Abundant literature confirms that intravenous (IV) and intra-articular (IA) administration of tranexamic acid (TXA) reduces blood loss in total knee arthroplasty (TKA). Oral formulations of TXA exhibit profound cost-saving benefits. However, comparisons of the clinical efficacy among three different modalities of TXA administration have not been previously investigated in the setting of TKA with no closed suction drain and tourniquet. A total of 180 patients undergoing TKA were randomized to receive 2-g oral T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 46 publications
2
26
0
1
Order By: Relevance
“…The results of this study suggested that no significant differences were found in blood-sparing management between oral and IV TXA. This finding is comparable to the findings of a recent meta-analysis that shown that oral TXA provided equivalent blood-sparing efficacy when compared with intravenous routes [ 23 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of this study suggested that no significant differences were found in blood-sparing management between oral and IV TXA. This finding is comparable to the findings of a recent meta-analysis that shown that oral TXA provided equivalent blood-sparing efficacy when compared with intravenous routes [ 23 ].…”
Section: Discussionsupporting
confidence: 88%
“…Based on the criteria described in the methods, 14 articles were further eliminated by reading the full articles, but some did not provide enough detail of outcomes of two approaches. Therefore, a final total of 9 studies [ 11 , 16 23 ] with included (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Hb drop and total blood loss were the primary outcomes in our meta-analysis. Many studies [ 23 , 25 , 27 31 ] demonstrated that oral TXA provides similar reductions in Hb drop and total blood loss in primary THA and TKA compared with IV TXA. The results of this study found no significant differences in Hb drop and total blood loss between oral and IV TXA.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that compared with IV administration, the use of oral TXA has the same effects as IV TXA on the transfusion rate following THA and TKA. [ 31 , 32 ]…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other surgical procedures, there was no good way to control bleeding of the bone surface of the femur and tibia after osteotomy during TKA and this will cause trouble for non-tourniquet TKA. The use of tranexamic acid and control of the blood pressure during the operation are effective methods to reduce the bleeding of the surgical field [8][9][10]. The former studies showed that the use of tranexamic can not only reduce the total blood loss during the perioperative period but also reduce the intraoperative blood loss [11,12].…”
Section: Introductionmentioning
confidence: 99%